Integrated mindfulness-based intervention to enhance performance-relevant psychological skills of elite badminton players - Doron, J.; Rouault, Q.; Jubeau, M.; Bernier, M. (14th World Congress of Sport Society Psychology, 2017)
While the application of mindfulness in the sport domain and its enhancement has exploded in recent years, mindfulness-based intervention programs for elite performers need further development and validation with the scientific rigor, appropriate openness, and sport-specific relevance (Sappington & Longshore, 2015). This study aimed to design an integrated program, drawn heavily on the MAC approach (Gardner & Moore, 2007), that suited the characteristics of the elite athletes and the specific demands of badminton. Specifically, the purpose was to evaluate the efficacy of an integrated mindfulness-based intervention (MBI) on the self-regulation attentional skills and performance of elite badminton players. 25 young elite badminton players from two French Badminton Federation`s National Training Centres were recruited for this study. They were assigned either to the experimental group (MBI program; n = 13, Mage = 16.15, SDage = 1.34) or to the active control group (Relaxation program; n = 12, Mage = 16.58, SDage = 1.24). All participants completed the online questionnaire (Mindfulness Inventory for Sport, Thought Occurrence Questionnaire for Sport, subjective performance) one week before the intervention (lasting 8 weeks) and two weeks after the end of it. The results of MANOVA yielded a significant multivariate effect of the intervention on the delta scores of self-regulation attentional skills (Wilk`s = .35, F(6, 18) = 5.57, p < .01, partial ?2 = .65). The results of univariate ANOVAs indicated that delta scores of refocusing (F (1, 23) = 4.03, p = .06) and task-irrelevant thoughts (F (1, 23) = 13.05, p < .01) differed significantly across the two programs. MBI may be a useful mental training intervention for improving self-regulation attentional skills. Considering that elite sport is quite different from other contexts, applying and integrating mindfulness-based interventions that successfully meet the demands of elite athletes and sport seems crucial. Integrated mindfulness-based intervention to enhance performance-relevant psychological skills of elite badminton players. Available from: https://www.researchgate.net/publication/318502916_Integrated_mindfulness-based_intervention_to_enhance_performance-relevant_psychological_skills_of_elite_badminton_players [accessed Aug 7, 2017].